Development of Authentic Assessment Instruments Oriented Reading Skills Based Language Literacy through the Scaffolding Model - Makhroji Makhroji; Irma Dewi Isda; Allif Syahputra Bania (AL-ISHLAH: Jurnal Pendidikan, 2021)
This research aims to develop an authentic assessment instrument product based on language literacy with a scaffolding model that is oriented towards reading skills. This research method uses research and development methods. The research results show that the preliminary research phase describes the results of curriculum analysis and student analysis. At the product development stage and validation by experts, the percentage of authenticity instrument eligibility consisting of three indicators is 82%. It can be concluded that the instrument is suitable for use in learning activities. The practicality stage given to 20 students in one of the Manyak Payed Public High Schools, Aceh Tamiang District, consisted of four alternative answers, 25% were declared practical. Thus, high school teachers are advised to use the scaffolding model as a solution to improve reading comprehension and language literacy skills.